Recent Advances in Nanotechnology for Dendritic Cell-Based Immunotherapy - Qian, Chen; Yang, Li-Jun; Cui, Hong (Frontiers in Pharmacology, 2020)
Dendritic cells (DCs) are the most important antigen-presenting cells that determine cancer immune responses by regulating immune activation and tolerance, especially in the initiation stage of specific responses. Manipulation of DCs to enhance specific antitumor immune response is considered to be a powerful tool for tumor eradication. Nanotechnology, which can incorporate multifunction components and show spatiotemporal control properties, is of great interest and is widely investigated for its ability to improve immune response activity against cancer and even for prevention and avoiding recurrence. In this mini-review, we aim to provide a general view of DC-based immunotherapy, including that involving the promising nanotechnology. Particularly we discuss: (1) manipulation or engineering of DCs for adoptive vaccination, (2) employing DCs as a combination to more existing therapeutics in tumor treatment, and (3) direct modulation of DCs in vivo to enhance antigen presentation efficacy and priming T cells subsequently. We comprehensively discuss the updates on the application of nanotechnology in DC-based immunotherapy and provide some insights on the challenges and opportunities of DC-based immunotherapeutics, including the potential of nanotechnology, against cancers.